Correction of Hypercholesterolemia in Primary and Secondary Prevention of Cardiovascular Diseases: Features and Controversial Issues - N. M. Akhmedzhanov; D. V. Nebieridze; A. S. Safaryan (Рациональная фармакотерапия в кардиологии)
The article discusses the current prevalence of hypercholesterolemia in everyday clinical practice in patients of different risk categories and approaches to its correction in the most frequently used clinical guidelines. High prevalence of hypercholesterolemia in practical health care with little change over time is shown. The existing problems of the practical implementation of the principles of a healthy lifestyle as the basis for reducing cardiovascular risk and possible solutions are described. Attention is focused on a low number of patients taking statins, and even less – reaching recommended target cholesterol levels. It is emphasized the validity of lower, compared to previous, target cholesterol levels in National recommendations on the correction of dyslipidemia in patients with proven atherosclerosis-related cardiovascular diseases as well as the feasibility in some cases of combined lipidlowering therapy (statins in combination with intestinal cholesterol absorption blockers, PCSK9 inhibitors, high doses of ethyl eicosopentaenoic acid). It is commented the need to prescribe statins in persons older than 75 years, but with a careful approach. Particular attention is paid to the use of statins in the primary prevention of cardiovascular complications. The validity of prescribing fixed moderate doses of statins for this purpose is discussed, which is both scientifically based and more realistic in practical terms.